2021
DOI: 10.3390/app11041610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Waste Blends with Sewage Sludge as a Potential Material Input for Pyrolysis

Abstract: In line with the requirements of the circular economy, the European Union’s waste management legislative changes also concern the treatment of sewage sludge. Although sewage sludge production cannot be prevented, its quantities may be reduced by the synergetic effect of energy recovery via choosing a proper technology. Sewage sludge is difficult to apply as fuel alone, because of its high moisture and ash content. However, its energy use will be increased by adding suitable waste materials (different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The development of energy-efficient technology and the shift to nonfossil energy sources, such as renewable energy sources, are expected and appear to be very promising [1,2]. Except, huge amounts of waste are produced by consumer society, and their disposal can negatively impact human health and ecosystems [3,4]. Agricultural residues can be used as fuels due to their energy potential and also the emission reduction compared to fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…The development of energy-efficient technology and the shift to nonfossil energy sources, such as renewable energy sources, are expected and appear to be very promising [1,2]. Except, huge amounts of waste are produced by consumer society, and their disposal can negatively impact human health and ecosystems [3,4]. Agricultural residues can be used as fuels due to their energy potential and also the emission reduction compared to fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…This laboratory pyrolysis unit consists of a reactor with a fixed grate that is heated by an electric spiral around the jacket. In our previous work [49], we focused on the comprehensive characterization of selected waste materials and tested various waste materials. The analyses provided very specific data regarding the modeling and optimization of the pyrolytic process, and therefore, we set the reactor temperature to 600 • C. As a result, we can expect higher-quality pyrolytic products.…”
Section: Pyrolysismentioning
confidence: 99%
“…The phenomenon of sludge "sticking" is beneficial in the proposed solution by facilitating the formation of the final product in the form of briquettes and increasing their compactness and durability. Kubonova et al [45] showed that sewage sludge is a very suitable binder for individual components of the alternative fuel, at the same time indicating that the moisture content of sewage sludge (about 72 wt.%) was an advantage for mixing with other types of waste.…”
Section: Sewage Sludge Valorizationmentioning
confidence: 99%